ANALISIS END USER COMPUTER SATISFACTION SISTEM PEMBUATAN E-KTP DI KECAMATAN KARTASURA KABUPATEN SUKOHARJO - Novia Titis Sulistyani; Sri Siswanti; Setiyowati Setiyowati (Jurnal Ilmiah SINUS, 2018)
The e-ID card service in Kecamatan Kartasura, Sukoharjo District has been running well, but people feel less satisfied with the service of making e-ID card by the sub-district officer. So it is necessary to know what factors affect the dissatisfaction. The research titled End User Computer Satisfaction analysis of e-ID card system in Kecamatan Kartasura Sukoharjo District was conducted to evaluate e-ID card making system in Kecamatan Kartasura Sukoharjo District.Factors in the process of making e-ID card is the influence of perception of content, accuracy, ease, and influence of timely perception toward the satisfaction of society. The method used in this system analysis is End User Computer Satisfaction. Population and sample of the research are 120 population in Kecamatan Kartasura Sukoharjo District. The result of the questionnaires is analyzed by using SPSS 15 with the classical assumption test, multiple linear regression, coefficient of determination and T-test and F-test.The results of the analysis revealed that 58.6% of the 4 independent variables of content, ease and timely affect the satisfaction of the population, while the accuracy does not affect the satisfaction of the population about the e-ID card system.